Comparative analysis of clinical, radiological and operative findings in acute abdomen - Ali, Mir Zeeshan; Maddu, Vamsee Krishna (International Surgery Journal, 2019)
Background: The term acute abdomen refers to signs and symptoms of abdominal pain and tenderness that often requires emergency surgical therapy. The objective of the present study is to compare pre-operative diagnosis based on clinical examination with the operative diagnosis in acute abdomen. Methods: Total 60 cases of acute abdomen who underwent laparotomy in a tertiary care hospital were analysed prospectively regarding clinical features and also assessed the diagnostic utility of radiological investigations like plain abdominal radiographs, ultrasonography and computed tomography. Results: Acute abdomen was most common in males and 2nd to 5th decade of life. Appendicitis was most common cause of acute abdomen followed by hollow viscus perforation and intestinal obstruction. Abdominal pain was the most common symptom. Tenderness was the most common sign. Diagnostic utility of x-ray is more in hollow viscus perforation and intestinal obstruction, whereas ultrasonography is diagnostic in 64.3%. Ultrasonography accurately diagnosed acute appendicitis in 74.2%, hollow viscus perforation in 50%, and intestinal obstruction in 60% of patients. 95% clinical accuracy was found when compared to intra operative diagnosis. Kappa is 0.912 (p<0.0001). Conclusions: Clinical judgement is key to diagnosis of acute abdomen and investigations are only supplementary and cannot replace the clinical decision.